Application of the Analytic Hierarchy Process (AHP) in Strategic Site Selection for Software Development Branch Expansion in Indonesia - Jumali, Muhamad Abdul; Andarmadi Jati Abdhi Wasesa; Harno Suntoko; Moch.Fatur Angga Pratma (Tibuana, 2025)
In an era where digital transformation dictates the survival of technology firms, selecting the optimal branch location is no longer a peripheral decision it is a strategic imperative. This study offers a powerful yet practical application of the Analytic Hierarchy Process (AHP) to evaluate potential expansion sites for a mid-sized software development company in Indonesia. By integrating expert judgments with location-specific criteria such as talent availability, infrastructure reliability, ecosystem proximity, and cost efficiency, the AHP model provides a structured, transparent, and replicable framework for decision-making. The results clearly identify Location A—an urban tech hub near major IT universities as the most strategic choice, significantly outperforming other alternatives. More than just a location ranking, this model demonstrates how conventional decision-making in software enterprise expansion can be elevated through applied analytical thinking. The study also proves that even without high-end analytics platforms, decision models built in common tools like Excel can yield robust and scalable insights. These findings carry immediate relevance for technology firms, policy planners, and academic researchers who seek to align operational expansion with long-term innovation and productivity outcomes in knowledge-based industries.